Socialization of Drug Dangers to Grow Healthy Culture Students Since Early Age At SD Negeri 66 Singkawang Timur Sanggau Kulor Sub-district in Year 2017 - Rika Wahyuni; Nurul Husna; Dina Anika Maharyani (International Journal of Public Devotion, 2018)
Dedication to the society is done in the form of socialization awareness of the dangers of drugs among students. This activity aims to provide understanding and knowledge of the dangers of drugs, in order to be able to avoid the abuse of drugs. This activity also aims to foster a healthy culture from an early age. The importance of growing a healthy culture among drug-free adolescents. Subjects of dedication to society activities are  the students grade VI in the 66 East Singkawang national School which amounted to 21 students. The socialization and mentoring activities were conducted by lecture, demonstration, discussion and practice with question and answer. Availability of adequate expert in providing socialization, the enthusiasm of the participants, support by goverment, RT and RW to the implementation of activities and financial support from STKIP Singkawan is a supporter of this dedication activity. Benefits to be gained by participants of this dedication activity is with these activities can provide awareness to students about the dangers of drugs. This socialization activity also can giving an understanding of the importance of healthy culture from an early age.